Theoretical study of electron affinities for selected diatomic molecules - Wróblewski, Tomasz; Hubisz, Krzysztof; Antonowicz, Józef (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Ab initio Hartree–Fock (HF) methods and different hybrid density functional theories (DFT), i.e., LSDA, BPV86, B3LYP, B3PV91, MPW1PW91, PBEPBE, PBE1PBE, HCTH, THCTH and TPSSTPSS, have been used to evaluate electron affinities (EAs) for selected diatomic molecules. Computations have also been made at the high level ab initio quadratic complete basis set (CBS-Q) method. The results show that HF calculations underestimate and DFT overestimate EA’s values in comparison to experimental data. We obtain the best agreement with experimental values of EA’s in DFT calculations with PBE1PBE, TPSSTPSS, THCTH and PBE1PBE functionals for OH, NaBr, LiBr and F2 molecules, respectively.
Optica Applicata, Vol. 40, 2010, nr 3, s. 601-608
Keywords: optyka; electron affinity; DFT methods